A comparative study of pre and post prandial blood pressure recordings on normotensives and hypertensives on treatment - Sequeira, Anitha; Rosario, David (International Journal of Research in Medical Sciences, 2017)
Background: The aim of the study was to study pre and post prandial BP recordings in normotensives and hypertensives on treatment above the age of 18 years. Methods: The study will be conducted on 50 normotensives and 50 hypertensives on treatment admitted to our hospital over a period of 3 months. The patients are randomly selected and the details of duration and antihypertensive are noted. Both systolic and diastolic blood pressure is measured in supine position of the right arm using digital electronic blood pressure monitor. BP recordings are taken 30 min before and 30 min after meals. Then fall in BP is recorded. Results: From this study we found that the mean systolic and diastolic blood pressure is higher in hypertensives than normotensive patients. The study was statistically significant which was found by paired t test. The post prandial fall in BP was significantly higher in hypertensives than normotensive patients. Probably hypertensives had reduced cardiac sympathetic tone which caused postprandial hypotension more than normotensive patients. Conclusions: Apart from pharmacological treatment, poor housing condition and illiteracy of the parents of these patients need to be addressed.